Species delimitation recovers undescribed Erpobdellidae (Annelida: Hirudinea) from USA and Türkiye - Saglam, Naim; Saunders, Ralph; Shain, Daniel H. (Magnolia Press, 2025)
Erpobdellid leeches are morphologically similar to each other and thus cause confusion in taxonomic identification. In particular, annuli, colour and eye patterns are very close across species which creates difficulties in external morphological resolution. Here we describe six new species of Erpobdellidae collected from North America and Europe based on morphological and molecular criteria. New species are formally designated Erpobdella farmensis sp. nov., Erpobdella haddonensis sp. nov., Erpobdella madenensis sp. nov., Dina sivricensis sp. nov., Dina takasensis sp. nov. and Trocheta kesirvenensis sp. nov. Phylogenetic comparisons were conducted with fragments of nuclear (18S rRNA) and mitochondrial [12S rRNA and cytochrome c oxidase subunit I (COI)] loci to confirm species separation. A global phylogeny with all available data in GenBank at the COI locus identified 49 recognized erpobdellid species, many of which occur regionally or are distributed globally.
Keywords: Clitellate; Hirudinid; Erpobdella; morphology; COI; new species